Slip effects on boundary layer flow and heat transfer along a stretching cylinder - Mukhopadhyay, Swati; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
An axi-symmetric laminar boundary layer flow of a viscous incompressible fluid and heat transfer towards a stretching cylinder is presented. Velocity slip is considered instead of the no-slip condition at the boundary. Similarity transformations are used to convert the partial differential equations corresponding to the momentum and heat equations into non-linear ordinary differential equations. Numerical solutions of these equations are obtained by the shooting method. It is found that the velocity decreases with increasing the slip parameter. The skin friction as well as the heat transfer rate at the surface is larger for a cylinder compared to those for a flat plate.
Keywords: boundary layer; stretching cylinder; partial slip; heat transfer; similarity solution